The impact of HIV infection on the physical activity levels, functional independence and exercise capacity in a group of South African adults taking or not taking antiretroviral medication - Kinsey, Kirsten Liza (My University, 2008)
Abstract Human Immunodeficiency Virus (HIV), a chronic medical condition characterized by cycles of wellness and illness, has the potential to decrease the physical activity levels and functional independence of infected individuals. Although antiretroviral therapy has been credited with improving and maintaining the immune status of infected patients by increasing cluster of differention 4 (CD4) count and suppressing viral load, the short- and long-term side effects of antiretroviral medication and the possible negative impact of these side effects on physical well-being have not yet been fully investigated. Therefore, I assessed the relationship between CD4 count, habitual physical activity levels and functional independence in a group of HIV positive South African adults either taking or not taking antiretroviral medication. I also compared the aerobic capacity, muscle strength and physical activity levels (activity counts) of age-matched black HIV negative females and HIV positive females who were taking antiretroviral medication. For the first part of the study, a Lifestyle and Physical Activity Questionnaire was completed by 186 black* male and female HIV positive outpatients who were recruited from a Johannesburg based antiretroviral roll out site. Of these patients, 121 were on first line antiretroviral treatment (median time of seven months), and 65 patients were not taking any medication. The questionnaire, as well as recording HIV history and current CD4 count, assessed each patient’s ability to independently perform one or more tasks of daily living as well as his/her monthly occupational, household and recreational physical activity levels. From the subjects’ responses, a total metabolic equivalent (MET) score for one month was calculated. The second part of the study assessed the full blood counts, aerobic capacity (submaximal bicycle ergometer test), lower limb strength (isokinetic dynamometry), hand grip strength (hand dynamometer) and seven day physical activity counts (actigraphy) of ten HIV positive black females recruited from the same Johannesburg antiretroviral roll out site. All of these patients had been taking first line antiretroviral treatment for a median time period of seven months. Ten HIV negative age-matched black females acted as their controls. From the questionnaire, significant correlations were observed between CD4 count and length of time on antiretroviral medication (P < 0.0001; r = 0.45), and between CD4 count and total monthly physical activity level (P = 0.0067; r = 0.20). Patients who considered themselves functionally independent had a significantly higher CD4 count that those patients who required help from others (P = 0.0031). The second part of the study revealed no significant difference in aerobic capacity, lower limb muscle strength (peak torque), handgrip strength and seven day physical activity counts between the female HIV positive patients and HIV negative controls. My results show that the use of antiretroviral medication (median time of seven months) increases CD4 count which translates into an increased habitual physical activity level and greater sense of functional independence. I have also shown that HIV positive females who are taking antiretroviral medication have an aerobic capacity, leg strength, handgrip strength and physical activity count which is not statistically different to their HIV negative counterparts. In this sample, the side effects associated with the administration of antiretroviral medication did not negatively impact on physical well-being. However, more research needs to be conducted on the possible physical activity limiting side effects of longer term antiretroviral medication administration, which may limit habitual physical activity levels. * Footnote: Race does not refer to any biological attributes but rather to the compulsory classification of people into the Population Registration Act. Although the act has been amended, these categories are still powerful and commonly used by the South African Government and statistical services.
Keywords: HIV; habitual physical activity; antiretroviral medication